Taxing Mobile Capital with Labor Market Imperfections - Wolfram F. Richter; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2001)
Taxing internationally mobile factors of production has been dismissed as an inefficient means of raising tax revenue. This paper addresses the question of whether it is efficient to tax capital at source when labor markets and the taxation of lumpsum income suffer from imperfections. Four reasons for taxing capital are identified: (i) institutional constraints rendering any taxation of profit income infeasible; (ii) market power in the demand for labor; (iii) market power in the supply of labor if it increases with the employment of capital; (iv) unemployment benefits that are not tied to net real wages. It is argued that the case for taxing capital is not particularly strong. By reinterpreting capital as energy the results are applicable to the discussion about ecological tax reforms.
Keywords: 330; Optimal taxation; factor mobility; labor market imperfections; ecological tax reform